Body Image Avoidance, Body Dissatisfaction, and Eating Pathology: Is There a Difference Between Male Gym Users and Non–Gym Users?. (March 2016) - Stapleton, Peta; McIntyre, Timothy; Bannatyne, Amy
With research highlighting the increasing prevalence and severity of body image and eating disturbances in males, particularly athletes and regular gymnasium users, the current study examined body image and eating disturbances in a sample of male gym users and non–gym users ( N = 180). Based on previous research, it was predicted that male gym users would report greater body image disturbance (e.g., body image avoidance and body dissatisfaction) and eating pathology, compared with non–gym users. Results of the study partially supported hypotheses, revealing body dissatisfaction and eating pathology were significantly increased in male gym users. However, no significant differences were observed in body image avoidance behaviors, though this is likely because of methodological limitations associated with psychometric measures selected. The study provides preliminary evidence that male gym users do experience subclinical eating and body image concerns, with some also experiencing clinically significant symptoms that could be precursors to the later development of an eating disorder. Results of the current study highlight the importance of educating key stakeholders within health and fitness centers, through community-based interventions, to increase awareness regarding male body image and eating disturbances.